ALEXANDER STREKAVIN’S (1889–1971) DRAWINGS OF MITAU – EVIDENCE FOR THE 19TH– EARLY 20TH-CENTURY INVENTIONS - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Mitau, the former capital of the Duchy of Courland and Semigallia, became the Courland Governorate centre with the Governor’s residence in a palace on an island formed by the Driksa, the branch of the Lielupe River, and great changes have taken place in this city. Artist Alexander Aleksandrovich Strekavin, who born in Mitau on 17 September 1889, studied art history, read books, investigated documents in the museum, listened to people’s stories and completed materials about events and the development of his native city. His drawings introduce with the new iron bridge for traffic and technical innovations – bicycles, the first car in the Baltics and the first phonograph in Mitau, clothes of citizens during the 19th century and at the beginning 20th century. Since the 1950s, six notebooks in Latvian with memoirs recalling by Aleksander Strekavin and an illustrative appendix – a collection of his drawings “The Atlas of Notes on Ancient Mitau” are in the funds of Jelgava History and Art Museum of Ģederts Eliass. Research object: drawings of artist Alexander Strekavin. Research goal: analysis of changes in Mitau during the 19th century and at the beginning 20th century. Research problem: Strekavin’s drawings stored in the funds of Jelgava History and Art Museum have not been studied. Research novelty: analysis of information on technical innovations included in “The Atlas of Notes on Ancient Mitau”. Research methods: studies of published literature, cartographic materials and archive documents.